Taraxacum amgense Kuvaev 1987 - Kirschner, Jan; Štěpánek, Jan (Zenodo, 2023)
3. Taraxacum amgense Kuvaev (1987: 203) Type :—[RUSSIA, Sakha Republic] Centr. Yakutia, Megino-Ka[n]galasskiy r-n., oduvanchikovo-osokovaya step na okraine alasa Chue sprava ot trakta na Amgu 20 km za r. p. Maiya [Sakha Republic, Megino-Kangalassky District, Mayya, ca. 61° 38’ N, 130° 07’ E], 8 Jun 1960, V. Kuvaev 15-1 (LE, no. det. 6054, holotype; isotype: MW, no. det. 20482). Etymology :— Named after the Amga River, Central Sakha Republic. Plants small, usually to 8–10 cm tall. Petiole narrow, usually narrowly winged, purplish, almost glabrous; plant base almost glabrous, with a well developed tunic. Leaves ± glaucous-green to greyish green, subglabrous, narrowly oblanceolate in outline, usually 3–6 (–9) × 1–2 cm, pinnatilobed to pinnatifid, lateral segments usually 2–3 (4), recurved, triangular-deltoid, ± subobtuse, distal margin subsigmoid or straight, usually entire, sometimes with a single short triangular tooth, proximal margin ± straight, entire; terminal segment usually triangular to helmet-shaped, obtuse to subobtuse, distal margin convex, usually entire, proximal margin straight, entire; interlobes broad, entire or with a single little tooth, not blotched; mid-vein suffused purple, at least proximally. Scapes usually brownish green, at least distally arachnoid, overtopping leaves. Capitulum [bright] yellow, ca. 2–3 cm wide. Involucre usually light olivaceousgreen, ca. 10 mm wide and rounded at base. Outer phyllaries not numerous, usually 10–11, appressed, not imbricate, ovate to ovate-lanceolate, usually 5–6 × 2–2.5 mm, surface olivaceous-green, distally darker and suffused purplish, border distinct, whitish-membranous, usually 0.2–0.4 mm wide, margin probably not ciliate, apex ± flat to callose. Outer ligules striped deep grey purplish outside. Stigmas yellow. Pollen absent. Achenes light red to light brownish red, ca. 3.0 [–3.5] mm long, body spinulose in upper 1/3, subgradually narrowing into a subconical cone ca. 0.4–0.5 [–1.0] mm long; beak ca. 4 mm long, pappus ca. 4 mm long, ± white. – ...